The year of the locust - Hayes, Terry (Bantam, 2023)
If, like Kane, you’re a Denied Access Area spy for the CIA, then boundaries have no meaning. Your function is to go in, do whatever is required, and get out again—by whatever means necessary. You know when to run, when to hide—and when to shoot. But some places don’t play by the rules. Some places are too dangerous, even for a man of Kane’s experience. The badlands where the borders of Pakistan, Iran, and Afghanistan meet are such a place—a place where violence is the only way to survive. Kane travels there to exfiltrate a man with vital information for the safety of the West—but instead he meets an adversary who will take the world to the brink of extinction. A frightening, clever, vicious man with blood on his hands and vengeance in his heart...
Keywords: Kane : (fiktiivinen hahmo); toimeksianto; kokeneisuus; väkivalta; työmatkat (matkustus); pahuus; kosto; viholliset; agentit; turvallisuuspalvelut; Etelä-Aasia; Lähi-itä